Predictive Value of Thrombin Time in Early Preeclampsia - Yuting Li; Yanli Chen; Hua Shu; Xiaoyun Zhang; Peng Li; Fengge Wang; Dongmei Man (Clinical and Experimental Obstetrics & Gynecology)
Background: Preeclampsia is a pregnancy-specific disease, which is easy to cause adverse outcomes in mother and child. Effective prediction of preeclampsia have important clinic al significance. This retrospective study aimed to investigate the utility of thrombin time during the first trimester as a predictive marker for preeclampsia. Methods: We meticulously examined the clinical characteristics of a cohort comprising 222 pregnant individuals with mild preeclampsia, 315 with severe preeclampsia, and 396 healthy pregnant women. Subsequently, we conducted both univariate and multiple regression analyses to discern variations in quantitative variables across these groups and to ascertain any discernible associations between thrombin time and the incidence of preeclampsia. Furthermore, we assessed the predictive performance of thrombin time by utilizing the receiver-operating characteristic (ROC) area under the curve (AUC). Results: Thrombin time exhibited a statistically significant prolongation in the preeclampsia cohort compared to the healthy pregnancy cohort (p < 0.05). This significance was maintained after adjusting for maternal age and gestation at testing in the logistic regression model. The AUC for thrombin time was found to be 0.953, with a commendable specificity of 97.28% and sensitivity of 92.48% in predicting preeclampsia. Conclusions: Our findings provide compelling evidence of a noteworthy association between prolonged thrombin time in the first trimester and an elevated risk of preeclampsia. The robust positive correlation underscores the potential of prolonged thrombin time as a predictive marker for the development of preeclampsia. Nevertheless, it is crucial to emphasize that further experimental studies are imperative to elucidate the underlying pathogenesis of thrombin time in the progression of preeclampsia.